Analisis Pemeriksaan MRI Brain Pada Kasus Vertigo Di Instalasi Radiologi Rumah Sakit Balimed Denpasar - Rama Yeni Ines Sirait; Ni Putu Jeniyanthi; Triningsih Triningsih; Burlian Mughnie (Lembaga Pengembangan Kinerja Dosen, 2024)
The background of this research is that vertigo is a symptom caused by disturbances in body balance due to the different locations of the lesions. Vertigo is not a disease but a symptomatic condition of vestibular system disorders. Evaluation of patients with audiovestibular disorders, sensorineural hearing disorders, tinnitus, and vertigo . Brain MRI is used to evaluate patients with audiovestibular dysfunction, including sensorineural hearing loss, tinnitus, and vertigo. This research method is descriptive qualitative research with a case study approach using a research design, namely observation, interviews and documentation which aims to find out why the T2 MATRIX 3D SPAIR sequence is needed for MRI brain examinations in vertigo cases at the Radiology Installation at Balimed Hospital, Denpasar. The data collection method was obtained using 3 Brain MRI patients, 3 radiology specialists and 3 radiographers. The results of this research show that the Magnetic Resonance Imaging (MRI) brain examination procedure in Vertigo cases at the Radiology installation at Balimed Hospital Denpasar uses the additional T2 MX3D SPAIR sequence for Vertigo cases because this sequence is able to show the nerve fibers in the brain. The conclusion is that the Magnetic Resonance Imaging (MRI) brain examination procedure in Vertigo cases at the Radiology installation at Balimed Hospital Denpasar does not require special preparation, only more attention is paid to the patient's condition, whether they are wearing braces or dentures because the two tools used will interfere with the results of the MRI image used. The reason for using the T2 MX3D SPAIR sequence is with the aim of adding diagnostic information from the image quality results in order to establish a diagnosis of many neurological disorders or nerve fibers, one of which is Vertigo.